Fetomaternal Doppler sonography for the prediction of perinatal outcome in term pregnancies complicated by gestational diabetes mellitus: does it have potential? - Graupner, Oliver; Rath, Caroline; Lecker, Linda; Ritgen, Jochen; Haller, Bernhard; Enzensberger, Christian (Ultrasound International Open, 2025)
Little is known about the benefit and interpretation of fetomaternal Doppler sonography in GDM for the prediction of an adverse perinatal outcome (APO). The aim of this study was to examine the performance of fetomaternal Doppler for APO prediction in pregnancies with GDM at term.This is a retrospective cohort study of singleton, non-anomalous fetuses of women with GDM, who primarily had a vaginal delivery attempt. Study inclusion also required no other major fetomaternal abnormalities that make placental dysfunction likely. Data on fetomaternal Doppler sonography including umbilical artery pulsatility index (PI), middle cerebral artery (MCA) PI, cerebroplacental ratio (CPR), mean uterine artery PI, cerebro-placental-uterine ratio (CPUR) was collected from 37+0 weeks on. Multivariate logistic regression analyses were performed using maternal characteristics, neonatal characteristics, and Doppler ultrasound parameters as independent variables with CAPO as a binary outcome. A total of n=88 cases were included. Nulliparity (p=0.032) and CPUR (p=0.052) were independent predictors of CAPO. However, CPUR had borderline significance. All other Doppler indices were not independent predictors of CAPO. The ability of CPUR alone (AUC=0.65, 95% CI 0.51 to 0.80) to discriminate between GDM pregnancies with and without CAPO was poor. This study shows that there is no significant clinical relationship between fetomaternal Doppler indices and CAPO among pregnancies with GDM. This raises the question regarding the extent to which fetomaternal Doppler indices, which reflect placental function, can be helpful for CAPO prediction in GDM pregnancies.
Keywords: fetomaternal Doppler; cerebroplacental ratio; uterine artery Doppler; adverse perinatal outcome; gestational diabetes mellitus